Patient blood management is a win-win: a wake -up call - Spahn, D.; Theusinger, O.; Hofmann, Axel (Oxford University Press, 2012)
Preoperative anaemia is frequent in surgical patients and increases postoperative mortality, major morbidity, and length of hospital stay. Poorly controlled bleeding and surgical blood loss can also contribute to these outcomes. Anaemia, blood loss, and liberal transfusion triggers are the main predictors for red blood cell (RBC) transfusion. RBC transfusion in turn is an additional independent predictor for adverse outcome and has therefore been referred to as the ‘second hit’ for the recipient. Transfusion outcomes include higher mortality, more ischaemic complications, organ dysfunction, infections, delayed wound healing, and increased length of hospital stay. Transfused patients may also be more likely to develop non-Hodgkin lymphoma. Interestingly, most of these complications are found after administration of just a single RBC unit.1011 Strict application of the Bradford-Hill criteria strongly suggests that the link between transfusion and adverse outcomes is causal and not just associative.